Liquid–liquid interface motion of a capsule motor powered by the interlayer Marangoni effect - Zhao, Guanjia (2013)
A novel thin capsule motor has been described in this report. It utilizes the Marangoni effect for the solid capsule to run at a water–oil interlayer, which has not been reported previously. Intrinsic and environment factors influencing the motion were investigated. It is also possible for the velocity, direction, and start/stop of the motion of the capsule to be manipulated.